Association between vascular endothelial growth factor polymorphism and recurrent pregnancy loss: A systematic review and meta-analysis. (April 2017) - Sun, Yaling; Chen, Min; Mao, Benyu; Cheng, Xianglin; Zhang, Xianping; Xu, Chuanxin
Abstract: Purpose: Some studies have reported that vascular endothelial growth factor (VEGF) genetic polymorphisms are associated with recurrent pregnancy loss (RPL), but the results are controversial. This study is aimed to quantify the strength of this association. Methods: A systematic review of the published literature from Medline, Springer, and China National Knowledge Infra structure (CNKI) databases was conducted and investigations of VEGF genetic polymorphisms in RPL were selected. We estimated the pooled odds ratio (OR) to assess this possible association. Results: Fifteen case-control studies comprising 2702 cases and 2667 controls and including five genetic polymorphisms (rs3025039, rs833061, rs15703060, rs2010963 and rs699947) were eligible for this meta-analysis. The overall analysis suggested that only two genetic polymorphisms (rs1570360, rs3025039) were associated with increased risk of RPL. A significant increased risk between VEGF rs1570360 polymorphism and RPL was only found under the dominant model in Caucasians (OR = 1.70, 95% CI 1.02-2.82, P = 0.04). Whereas, we found that VEGF rs3025039 polymorphism was significantly associated with RPL both under the dominant and recessive model in East Asians, and their summary odd ratios and 95% CIs were 1.26, 1.04-1.53, P = 0.02 and 2.94, 1.80-4.83, P = 0, respectively. Conclusions: This meta-analysis showed that only rs1570360 (especially in Caucasians) and rs3025039 (especially in East Asians) may be risk factors for RPL.